Alpha-1-antitrypsin deficiency in children: a 10-year case study from a tertiary hospital - Joana Carvalho Queirós; Rita Gomes; Bebiana Sousa; Júlia Vasconcelos; Ermelinda Santos Silva; Maria Guilhermina Reis (Portuguese Journal of Pediatrics)
Introduction and Objectives: Alpha-1-anti-trypsin (A1AT) is a glycoprotein mainly produced in the hepatocyte. A1AT deficiency is one of the most prevalent genetic disorders and the spectrum of it related diseases is quite wide. Severe A1AT deficiency predisposes individuals to Chronic Obstructive Pulmonary Disease (COPD) and liver disease. Our aim was to characterize clinically, biochemically and phenotypically a sample of pediatric A1AT-deficient (A1ATD) patients and to investigate whether there was any lifestyle change after diagnosis. Additionally, it was our goal to promote awareness to A1ATD among the medical community and to encourage the creation of a national pediatric registry and collaboration in the European registry. Methods: An observational retrospective study with analysis of the clinical records of all pediatric patients that had AAT measurement in our tertiary center between January 2010 and December 2019 and revealed levels < 93 mg/dl. Results: We enrolled 203 patients, 125 (61.6%) males. Median age at diagnosis was 2.93 years (IQR: 0.73-6.31). There was a family history in 18 patients (8.9%). The assessment of serum A1AT levels was motivated by: respiratory disease (121/203; 59.6%), liver disease (39/203; 19.2%), and family screening (6/203, 3%). The median serum A1AT concentration was 79 mg/dl (IQR: 68-85.4). Phenotyping in 47 patients (23.2%) revealed: MZ (12; 28.6%), MS (10; 23.8%) and ZZ (7; 16.7%). The prevalence of smoking exposure before and after diagnosis was 23.6% and 20.1%, respectively. Only 33% of patients underwent influenza vaccination after diagnosis. Discussion: In our sample, there was no significant change in the smoking exposure before and after diagnosis. It would be important to evaluate the impact of early diagnosis and the lifestyle changes on the long-term prognosis, as well as the creation of follow-up protocols in pediatric age. Larger, multicentric studies are needed to determine the real prevalence, the frequency of the main associated mutations, as well as the clinical consequences and follow-up approach required.